2023
DOI: 10.1186/s12864-023-09336-y
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive meta-QTL analysis for dissecting the genetic architecture of stripe rust resistance in bread wheat

Abstract: Background Yellow or stripe rust, caused by the fungus Puccinia striiformis f. sp. tritici (Pst) is an important disease of wheat that threatens wheat production. Since developing resistant cultivars offers a viable solution for disease management, it is essential to understand the genetic basis of stripe rust resistance. In recent years, meta-QTL analysis of identified QTLs has gained popularity as a way to dissect the genetic architecture underpinning quantitative traits, including disease re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 107 publications
1
13
0
Order By: Relevance
“…Even though it is challenging to compare the positions of QTLs from different studies because of the different mapping methodologies, marker systems, and mapping populations employed, some QTLs found in this study coincided with the mapping positions of previously reported yellow rust resistant genes in the literature. Similar to the current study, several earlier studies reported yellow rust-resistant QTLs on 1A ( Fu et al., 2019 ; Tehseen et al., 2020 ; Yao et al., 2021 ; Baranwal et al., 2022 ; Bouvet et al., 2022 ), on 1B ( Losert et al., 2017 ; Alemu et al., 2020 ; Baranwal et al., 2022 ), on 1D ( Long et al., 2019 ; Jia et al., 2020 ; Zhang et al, 2021 ; Baranwal et al., 2022 ; Kumar et al., 2023 ) on 2A ( Tehseen et al., 2020 ; Zhang et al., 2021 ; Zhang et al., 2021 ; Baranwal et al., 2022 ), on 2B ( Li et al., 2020 ), on 2D ( Mu et al., 2020 ; Baranwal et al., 2022 ), on 3A ( Tehseen et al., 2022 ), on 3B ( Zegeye et al., 2014 ; Kumar et al., 2020 ), on 3D ( Bouvet et al., 2022 ), on 4A ( Mu et al., 2020 ), on 4B ( Alemu et al., 2020 ), on 4D ( Rollar et al., 2021 ), on 5A ( Zhang et al., 2021 ), on 5B ( Lu et al., 2014 ), on 5D ( Zhang et al., 2021 ), on 6A ( Baranwal et al., 2022 ), on 6B ( Zhang et al., 2021 ) on 7A ( Yel et al., 2019 ; Alemu et al., 2020 ; Tehseen et al., 2020 ; Baranwal et al., 2022 ), and on 7D ( Long et al,. 2019 ; Rollar et al., 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…Even though it is challenging to compare the positions of QTLs from different studies because of the different mapping methodologies, marker systems, and mapping populations employed, some QTLs found in this study coincided with the mapping positions of previously reported yellow rust resistant genes in the literature. Similar to the current study, several earlier studies reported yellow rust-resistant QTLs on 1A ( Fu et al., 2019 ; Tehseen et al., 2020 ; Yao et al., 2021 ; Baranwal et al., 2022 ; Bouvet et al., 2022 ), on 1B ( Losert et al., 2017 ; Alemu et al., 2020 ; Baranwal et al., 2022 ), on 1D ( Long et al., 2019 ; Jia et al., 2020 ; Zhang et al, 2021 ; Baranwal et al., 2022 ; Kumar et al., 2023 ) on 2A ( Tehseen et al., 2020 ; Zhang et al., 2021 ; Zhang et al., 2021 ; Baranwal et al., 2022 ), on 2B ( Li et al., 2020 ), on 2D ( Mu et al., 2020 ; Baranwal et al., 2022 ), on 3A ( Tehseen et al., 2022 ), on 3B ( Zegeye et al., 2014 ; Kumar et al., 2020 ), on 3D ( Bouvet et al., 2022 ), on 4A ( Mu et al., 2020 ), on 4B ( Alemu et al., 2020 ), on 4D ( Rollar et al., 2021 ), on 5A ( Zhang et al., 2021 ), on 5B ( Lu et al., 2014 ), on 5D ( Zhang et al., 2021 ), on 6A ( Baranwal et al., 2022 ), on 6B ( Zhang et al., 2021 ) on 7A ( Yel et al., 2019 ; Alemu et al., 2020 ; Tehseen et al., 2020 ; Baranwal et al., 2022 ), and on 7D ( Long et al,. 2019 ; Rollar et al., 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…Meta-analyses of QTLs associated with a variety of traits have been recently conducted in different crops such as wheat ( Kumar et al, 2021 ; Kumar et al, 2022 A. C. ; Kumar et al, 2023 S. ; Saini et al, 2021 ; Saini et al, 2022 ; Tanin et al, 2022 ), rice ( Sandhu et al, 2021 ; Kumari et al, 2023 ), barley ( Akbari et al, 2022 ), common bean ( Shafi et al, 2022 ), pigeon pea ( Halladakeri et al, 2023 ), including maize ( Kaur et al, 2021 ; Sheoran et al, 2022 ; Wang et al, 2022 ; Gupta et al, 2023 ; Karnatam et al, 2023 ), for diverse traits, including both yield-related traits ( Semagn et al, 2013 ; Wang Y. et al, 2016 ; 2020 ; Chen et al, 2017 ; Zhou et al, 2020 ) and quality traits ( Jin et al, 2013 ; Dong et al, 2015 ). However, there is currently no comprehensive study on the genomic regions influencing both grain quality and yield in maize.…”
Section: Discussionmentioning
confidence: 99%
“…Among these genes, TraesCS7D02G217700 has been proposed as a candidate gene conferring resistance to LR. Furthermore, Kumar et al [ 35 ] used high-confidence meta-QTLs to identify three GT-encoding genes ( TraesCS2B02G012000 , TraesCS5A02G305000 and TraesCS5A02G305100 ) in wheat that may be linked to stripe rust resistance. In a previous study [ 10 ], we showed that in rye inoculated with a semi-compatible Prs isolate, the protective role of GT may be related to the conversion of DIBOA to DIBOA glucoside, the content of which increased at 24 hpt and then decreased at 48 hpt.…”
Section: Discussionmentioning
confidence: 99%